The impact of information technology on the performance of clinical pharmacy services. - Tully M (Journal of Clinical Pharmacy & Therapeutics, 2000)
Electronic patient records are now being developed to assist in the clinical management of patients within secondary care. This paper reviews how various types of information technology used in these electronic patient records can improve the performance of clinical pharmacy services. The different levels of information technology support for some of the main aspects of clinical pharmacy services are described. How the impact and outcome of information technology support for these services should be evaluated are discussed. The human and technological factors that must be considered to ensure that the implementation succeeds and the potential benefits are realized are examined.